THE IMPORTANCE OF PEDAGOGICAL CULTURE IN SOLVING EDUCATIONAL PROBLEMS IN THE ENGLISH LANGUAGE TEACHING - Ismailov A.R.; Dosaliev K.S. (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: The effectiveness of the educational process depends not only on the content of instruction and methodological approaches but also on the level of pedagogical culture demonstrated by the teacher. In modern education, where teachers face challenges such as declining student motivation, communication barriers, cultural diversity, and the growing influence of digital technologies, pedagogical culture becomes a key factor in resolving pedagogical problems. This article examines the role of pedagogical culture in English language teaching and demonstrates how professional competence, ethical behavior, communicative skills, and intercultural awareness contribute to creating a productive learning environment and improving educational outcomes.